HYDROCHEMICAL CONDITION OF GROUD WATER WITHIN THE CITY OF TATARBUNARY OF ODESSA REGION - Miedviedieva, O.; Koshliakova, I.; Dyniak, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The hydrochemical state of soil aquifers within the city of Tatarbunary, Odessa region is considered. Currently, water quality is an urgent problem and is relevant not only for the city but also for the entire Odessa region and the country as a whole. In addition, due attention is not given to the problems of a small town or village, which exacerbates the problem. There are no surface water sources in Tatarbunary. The waters of artesian wells on the Upper Sarmatian aquifer are used for both domestic and drinking needs. The object of research is the groundwater of the first aquifers from the surface. The subject of research is the chemical state of groundwater within the city. An objective assessment of the state of waters within the city can be provided only on the basis of observations of the hydrochemical composition of groundwater. To do this, it is necessary to conduct systematic monitoring observations: to have a network of observation points and appropriate cartographic material. The study was conducted in five phases, which included field and in-house work, sampling of water for chemical analysis and processing of the results. The chemical composition of water in 23 wells within the city of Tatarbunary was studied. 16 indicators were identified and waters were assigned to a certain class and type of water according to the relevant indicators, taking into account the classification of Alokin. In addition, the results of the analyzes were compared with the indicators of maximum permissible concentrations (MPC) for water supply from wells. According to the test results, two types of water were noted, namely water of moderate mineralization and highly mineralized water. All of them belong to the class of sulfate waters. Of these were dominated by sodium ion. It was found that water in many respects exceeds the MPC and is unsuitable for drinking water consumption (nitrite and phosphate content within the MPC). According to the determined content of harmful substances in water, it is necessary to eliminate their presence by water treatment – installation of filters on water sources or switching to bottled water and it is necessary to adopt regulations on source maintenance and user responsibility for pollution.